Studies of physical and technical characteristics of biowaste as components of gasification - Osmak, Alexei; Seryogin, Oleksandr (My University, 2014)
Proved promising use of plant biomass as a fuel due to the widespread introduction of bioenergy technologies. Justified the use of biomass for heat and electricity. The basic reasons for the use of organic materials as a source of renewable energy. The examples of industrial use of energy from biomass in the EU. Investigated the variation of the calorific value of the product gas from the humidity of the incoming raw materials. By experiment investigated the suitability of various types of plant biomass (sunflower husks, hulls of buckwheat and oats) to further thermochemical conversion for alternative fuel.The results of the technical analysis (moisture, ash, calorific value) of a number of analytical samples of agricultural waste.Studied the elemental composition of certain types of plant material, which suggests that these agricultural residues are highly reactive fuel with a high yield of volatiles.
Keywords: біомаса; биомасса; biomass; лузга соняшника; лузга подсолнечника; sunflower husks; лушпиння гречки; шелуха гречки; buckwheat husks; лушпиння вівса; шелуха овса; oat hulls; деревина; древесина; wood; торф; peat; кафедра електропостачання і енергоменеджменту